Supporting Actors. - Mazzaferro, Alexander (Transactions of the American Philosophical Society, 2024)
The article focuses on the significant yet often overlooked contributions of Jane Aitken, an early American printer, to the American Philosophical Society (APS) and its Transactions. Despite the near-total exclusion of women from the Society during its first century, Aitken played a crucial role in the production and dissemination of its publications, including binding hundreds of copies and independently printing volume 6 of the Transactions. Her work not only facilitated the circulation of new scientific knowledge but also highlighted the contributions of women in the Enlightenment, challenging the narrative that primarily recognizes male figures in science. Aitken's story reflects the broader theme of "invisible assistants" in the history of science, emphasizing the importance of diverse contributions to intellectual culture.